2022
DOI: 10.3390/logistics6030060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Activities That Make Up the Reverse Logistics Processes and Their Importance for the Future of Logistics Networks: An Exploratory Study Using the TOPSIS Technique

Abstract: Background: The wide variety of terms that converge in reverse logistics have been more evident and discussed in the current context of the literature, such as reverse channels, reverse supply chain, closed-loop supply chain, and circular supply chain. Regarding this, this paper aimed to investigate the level of uncertainty about the activities that make up the Reverse Logistics process in the opinion of professionals working in this area in Brazil, to develop a discussion relating to the sustainable developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
(165 reference statements)
0
6
0
1
Order By: Relevance
“…A dotação de processos eficientes de logística como ferramenta de gestão nas empresas poder trazer diversos benefícios como levar à diminuição dos custos operacionais, refletindo diretamente no preço da mercadoria ou serviço, satisfazendo e fidelizando clientes, e o mais importante para uma empresa, aumentar a lucratividade e produtividade (Martins et al, 2022) Ballou ( 2006) logística é o processo de planejamento do fluxo de materiais, que tem como objetivo principal a entrega dos produtos na qualidade desejada e no tempo certo, otimizando recursos e aumentando eficiência nos serviços. Consiste em criar valor, seja para os clientes, fornecedores, ou para todos os envolvidos diretamente com a empresa.…”
Section: Logísticaunclassified
“…A dotação de processos eficientes de logística como ferramenta de gestão nas empresas poder trazer diversos benefícios como levar à diminuição dos custos operacionais, refletindo diretamente no preço da mercadoria ou serviço, satisfazendo e fidelizando clientes, e o mais importante para uma empresa, aumentar a lucratividade e produtividade (Martins et al, 2022) Ballou ( 2006) logística é o processo de planejamento do fluxo de materiais, que tem como objetivo principal a entrega dos produtos na qualidade desejada e no tempo certo, otimizando recursos e aumentando eficiência nos serviços. Consiste em criar valor, seja para os clientes, fornecedores, ou para todos os envolvidos diretamente com a empresa.…”
Section: Logísticaunclassified
“…In addition, the analysis of the latest sources [41][42][43][44][45][46][47][48][49] also showed that the greatest attention is paid to the circular economy and civilian logistics, as well as aspects of reverse logistics in it, while such a significant aspect as the interaction of circular and reverse logistics in the military sector is almost not examined. Therefore, this gap allows us to assume and inspire further discussion at the level of scientific research.…”
Section: Disposalmentioning
confidence: 99%
“…Economic and financial factors are related to the impact on company profitability (Abbasi and Nilsson, 2012;Centobelli et al, 2017). The economic aspect is usually perceived as a key barrier because the financial benefits of GLPs are often achieved only in the long term, and Murphy and Poist (2000), Lieb and Lieb (2010), Martins et al (2022) Personnel training to increase awareness Murphy and Poist (2000), Lieb and Lieb (2010) companies fear short term cost increases (Colicchia et al, 2013;Perotti et al, 2022). GLPs also require significant investments, which represent important barriers when dedicated assets must be acquired by companies (Gotschol et al, 2014;Hrovatin et al, 2016).…”
Section: Factors Influencing Glps Adoptionmentioning
confidence: 99%
“…Reflecting the importance and the urgency of the problem for practitioners, the academic literature relating to green logistics has also grown rapidly (Singh and Trivedi, 2016; Martins et al. , 2022; Meyer, 2020).…”
Section: Introductionmentioning
confidence: 99%